Distribution of Mean Annual Percipitable Water in Nigeria - Iniobong Anthony Udo; Charity U. Okujagu (International Journal of Science and Engineering, 2014)
Mean monthly precipitable water values from twenty seven state capitals and Federal Capital Territory, Abuja are determined using a ten year monthly meteorological parameter- average surface temperature.  The results are then presented on annual average precipitable water map.  The map shows that location with high topography has lowest value of precipitable water while location with plain terrain has highest value of precipitable water